ACADEMIC PROGRAMME COMPARISON FEATURE IN E-COURSE OUTLINE SYSTEM - Chiong, Poh Ching (Universiti Malaysia Sarawak (UNIMAS), 2014)
This report proposes an academic programme comparison feature of the E-Course outline system in University Malaysia Sarawak (UNIMAS). The proposed feature provides convenience and e//icienev to the course coordinator, program coordinator in calculating the percentage of change and listing the components that have been revised. Apart from that, in order to enable the comparison. Jeature to be implemented, improvement to the current E-course outline system database design is also one of the focuses on developing the proposed feature. Improvement to the database design is needed because currently, the database of E-Course outline system is only available for one record, fr each programme and programme course outline. Therefore, there is not option to store and retrieve the multiple version of academic programme and programme course outline in the system.